A review of Tychobythinus theryi species group with description of a new species from Algeria (Coleoptera, Staphylinidae, Pselaphinae) - Sabella, Giorgio; D’urso, Vera; Nouira, Said; Souissi, Rhida; Besuchet, Claude (Zootaxa, 2013)
The seven species belonging to Tychobythinus theryi group are revised. Tychobythinus theryi (Guillebeau, 1894), Tychobythinus bordei (Peyerimhoff, 1919), Tychobythinus longipalpis (Normand, 1930), Tychobythinus normandi (Jeannel, 1956) and Tychobythinus peyerimhoffi (Jeannel, 1956) are redescribed and illustrated, and Tychobythinus besucheti Sabella sp. n. from north-eastern Algeria is described and illustrated. The lectotypes are designated for Tychobythinus theryi, Tychobythinus bordei and Tychobythinus peyerimhoffi. A key for species identification is provided.